2007
DOI: 10.1117/12.752839
|View full text |Cite
|
Sign up to set email alerts
|

Development of technologies for layer-by-layer laser synthesis of 3D parts in Russia and Belarus

Abstract: A brief overview of currently available methods applied in laser synthesis of 3D parts is presented, which range from stereolithography making use of liquid photopolymers to selective laser sintering of metal powders aimed at production of the parts of complex topology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…The aim of research was to study the possibilities of growing workpieces with a uniform finegrained structure in laser melting of metal powders of heat-resistant nickel-based alloys, designed for figurine-shaped parts by layered laser fusion. The experiment involved building-up of an average power of up to 2.5 kW and 3-coordinate table manipulator [6][7][8]. Specifications of "Hybrid" laser -Industrial waveguide CO 2 -laser are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The aim of research was to study the possibilities of growing workpieces with a uniform finegrained structure in laser melting of metal powders of heat-resistant nickel-based alloys, designed for figurine-shaped parts by layered laser fusion. The experiment involved building-up of an average power of up to 2.5 kW and 3-coordinate table manipulator [6][7][8]. Specifications of "Hybrid" laser -Industrial waveguide CO 2 -laser are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…В ИПЛИТ РАН в течение последних лет, опираясь на богатейший опыт технологических работ по модификации поверхности, закалке, наплавке и легированию, разработан лазерный комплекс аддитивных технологий (селективное лазерное спекание -СЛС материалов и изделий из металлических порошков). Комплекс основан на волноводном многоканальном СО 2 -лазере "Гибрид" (рис.4) со средней мощностью до 2,5 кВт и трехкоординатном столе-манипуляторе [6][7][8]. Технические характеристики лазера "Гибрид" -технологического волноводного СО 2 -лазера приведены в табл.…”
Section: экспериментальный комплекс для аддитивных технологий на базеunclassified